Preparation of poly(glyco1ic acid)bonded fiber structures for cell attachment and transplantation - Mikes, A.G.; Bao, Y.; Cima, L.G.; Ingber, D:E.; Vacanti, J.P.; Langer, R.
A novel method was developed to prepare threedimensional structures with desired shapes used as templates for cell transplantation. The produced biomaterials are highly porous with large surface/volume and provide the necessary space for attachment and proliferation of the transplanted cells. The processing technique calls for the formation of a composite material with nonbonded fibers embedded in a matrix followed by thermal treatment and the selective dissolution of the matrix. To evaluate the technique, poly(glyco1ic acid)(PGA)fiber meshes were bonded using poly(L-lactic acid)(PLLA)as a matrix. The bonded structures were highly porous with values of porosity up to 0.81 and area/volume ratios as high as 0.05 pm-'.